An Analysis of Translation Technique in Translating “Looking For Alaska” Novel Written by John Green - Inang Regita Cahyani Sunani; Novriyanto Napu; Jefriyanto Saud (Transbahasa, 2022)
This research analyzes translation techniques used in translating Looking for Alaska novel written by John Green. A qualitative method is employed in discovering the results, where it is conducted by employing note-taking in order to collect the data. In analyzing the data, this research utilized document analysis for reviewing or evaluating the selected document, which in this case, the translated novel. After conducting this research, it is found that this novel is translated by using ten types of technique, namely adaptation, amplifiction, borrowing, calque, compensation description, estabilish equivalent, generalization, literal translation, and variation. Furthermore, the most used technique in translating the Looking for Alaska novel is literal translation with the discovered cases being 140 and since this technique is constantly used in translation, this number is only the representation of it because it is safe to assume that the translator usually resorted to this technique presumably due to it is being default way of translating a text.